Optimization of Laying Duck Feed Combinations Using the COCOSO Method - Harlan Kurnia AR; Raditya Abdillah Putra; Dwi Andini; Nazwa Chairunnisa Hamid Siagian; Muhammad Alfaridho; Hazlah Aqillah (Ali Institute or Research and Publication, 2026)
The productivity of laying ducks is highly influenced by feed composition and nutrient quality. Inappropriate feed combinations may reduce production performance and increase operational costs. This study aims to determine the optimal feed combination for laying ducks using the Combined Compromise Solution (COCOSO) method by considering nutritional, production, and economic criteria. This study evaluates 15 alternative feed combinations consisting of commercial pellets and supplementary ingredients such as fine bran, ground corn, soybean meal, mineral mix, vitamin mix, and fish meal. Seven criteria were used, including protein, calcium, feed cost, egg production (HDP), health, palatability, and Feed Conversion Ratio (FCR), which were classified into benefit and cost attributes. The analysis process includes decision matrix construction, normalization, criteria weighting, and ranking using three COCOSO aggregation strategies to obtain compromise scores. The results indicate that differences in feed performance are clearly identified through multi-criteria evaluation. The best alternative achieved the highest COCOSO score of 0,940, indicating the most optimal balance between nutritional quality, production performance, feed efficiency, and cost. This study concludes that the COCOSO-based Multi-Criteria Decision Making (MCDM) approach is effective for supporting decision-making in livestock nutrition. The proposed model provides a structured, objective, and practical tool for farmers and practitioners to optimize feed strategies and improve production efficiency.